The AIDS Model of Indonesia Tourism Price Competitiveness - Santi Singagerda , Faurani; Rafiq, Muhammad; Wibaselppa, Anggawidia (International Journal of Psychosocial Rehabilitation, 2020)
According to World Economic Forum (WEF) data of 2013, Indonesia’s tourism price index is ranked 9 out of 140 countries in the world far beyond Malaysia and even Thailand. However, a low-price level does not guarantee high foreign exchange earnings of a tourism destination. If the demand for a destination is price inelastic, the price reduction strategy cannot increase the foreign exchange earnings of a destination. Therefore, the appropriate demand elasticity approach is used to measure tourism competitiveness in terms of price. This research uses model of Almost Ideal Demand System (AIDS). The value of price elasticity shows that Indonesia is more competitive than Thailand even by Australian and American tourists and more competitive than Malaysia by American tourists. The results also show that the price of tourism is the main determinant affecting the allocation of tourist spending in the three destinations. By knowing the position of Indonesia’s competitiveness of tourism to competitor countries, it is necessary to apply different promotion strategies for each country of the tourist market according to its demand characteristics. This research proposes policy recommendation in the form of the need to apply the increasing of foreign exchange earnings of tourism sector in Indonesia, among others the need of pricing strategy, domestic inflation stability, monetary price trend of competitor country, and tourism industry cooperation.